Parasitofauna of Brown Noddies, Anous stolidus (Charadriiformes, Laridae) on the Coast of Sergipe, Northeastern Brazil - Alves, André Mota; Figueiredo, Larissa Mello; Nascimento, Claudia Carvalho do [UNESP]; Sarmento, Carlos Alberto Palmeira; Medeiros, Iara Gama de; Brito, Elaine Knupp de; Parente, Jociery Einhardt Vergara; Borges, João Carlos Gomes; Lima, Victor Fernando Santana [UNESP]; Batista, Marcus Vinicius de Aragão (Springer Nature, 2025)
The brown noddy (Anous stolidus) is a charadriiform seabird of the family Laridae that inhabits tropical and subtropical rocky and sandy areas across all oceans. It can often be observed at sea, foraging alongside flocks of boobies and other terns. Although it is a marine bird, it feeds at the surface and does not dive, unlike most tern species. Parasitological studies involving this species remain scarce in the scientific literature. This study aims to document the helminth fauna present in seven specimens of brown noddies (Anous stolidus), stranded along the coast of Sergipe in the Northeast of Brazil. The specimens collected between April and June 2024 were analyzed, revealing the presence of various helminth parasites, including the genera Reighardia, Renicola, and Contracaecum. The research expanded the host range for the pentastomid Reighardia sternae, adding the genus Anous and the species A. stolidus, marking the first record of this parasite in the region. Contracaecum. magnipapillatum is reported for the first time on the Brazilian coast. Additionally, parasitism by Renicola sp. and Contracaecum pelagicum was recorded, broadening knowledge of these helminths geographic distribution in Brazil’s seabirds. The observed parasitic intensity was low, but the damage caused to the hosts may have implications for the health of seabird populations in the region, as parasitic infections can impair the gastrointestinal and respiratory systems of the birds. Although the sample size of birds was small, this study highlights the importance of continuous monitoring of migratory seabirds in order to identify parasite species that may affect populations of species such as A. stolidus. Future research needs to integrate a set of molecular, morphological, and environmental tools to better understand the ecological and health impacts of parasitism, thereby contributing to the conservation of these vulnerable populations.